Screening for resistance to black rot in a Spanish collection of Brassica rapa. Issue 5 (22nd July 2015) - Lema, Margarita; Cartea, María Elena; Francisco, Marta; Velasco, Pablo; Soengas, Pilar; Chevre, A.‐M.
Abstract Productivity and quality of crops of Brassica rapa L. in north‐western of Spain are highly affected by black rot, caused by the bacterium Xanthomonas campestris pv. campestris (Pammel) Dowson (Xcc). Several races of Xcc have been described in this area, being the race 6 the most frequent in B. rapa crops and races 1 and 4 the most frequent in B. oleracea crops. The control of the disease can be aided by the employment of resistant varieties. The aim of this work was to find sources of resistance to Xcc in a collection of open‐pollinated varieties of B. rapa from north‐western Spain. Resistance was evaluated in 191 landraces. Partial resistance to races 6, 1 and 4 and complete resistance to race 4 were identified in several landraces. Several accessions exhibited partial resistance to the three races. Sources of resistance were identified in landraces of different crops of the species (turnips, turnip greens and turnip tops). These landraces could be grown after selection for resistance or they can be donors of resistance genes in breeding programmes.